Dampak Pemberhetian Ekspor Beras Dari Negara-Negara Pengekspor Utama Terhadap Ketahanan Pangan Indonesia - Naira Afshari Putri; Raden Roro Aura Putri Indira; Vany Seftiani Kurnia (Pusat Riset dan Inovasi Nasional, 2024)
The development of rice production in Indonesia is very important to support national economic growth. Considering the importance of rice as a fundamental element in the national food system, rice is the most important food ingredient that needs to be produced a lot. In Indonesia, more rice is produced than people consume. To maintain and increase food security, as well as close the gap between domestic consumption and local rice production, the government is still importing rice. Apart from that, rice imports also aim to maintain rice supplies and keep rice prices stable. So what happens if Indonesia no longer accepts rice imports from major rice exporting countries such as Vietnam, Thailand and India? This research aims to provide in-depth insight into the impact of stopping rice exports and its implications for food security in Indonesia. The data obtained used descriptive statistical analysis techniques to compare the amount of rice consumed, produced and imported into Indonesia. The findings of this research indicate that Indonesia's food security will not be significantly impacted if major rice exporting countries stop sending rice to Indonesia. This is because over the last five years (2018–2022), rice production has exceeded Indonesia's rice consumption. However, if the level of rice production in Indonesia at any time decreases, rice supplies will not be sufficient and the price of rice will increase significantly.